Comparison of Methods of Solving Improper Integrals Using Methods of Integration and the Gamma and Beta Functions - Aml Ali; Suad Alkhammas (AlQalam Journal of Medical and Applied Sciences, 2024)
In this paper, we study Improper Integrations and methods of solving them using the usual integration methods and comparing their solution using Gamma and Beta Functions, where we touched on the study of the types and properties of Improper Integrations and the study of convergence tests for them. Our study focused on the importance of Gamma and Beta special functions in terms of making Improper Integrations with the comparison of solutions using accepted integration methods. The study relied on collecting data from international books, references and journals, which led us to results that confirm that Gamma and Beta contribute in a very wonderful way in facilitating many difficult practical calculations related to subject of the study. It also provides a successful way to save time and effort to solve problems of Improper Integrations. Some of these integrations can only be solved using the Gamma and Beta functions. في هذا البحث ندرس التكاملات المعتلة وطرق حلها باستخدام طرق التكامل المعتادة ومقارنة حلها باستخدام دالتي جاما وبيتا، حيث تطرقنا إلى دراسة أنواع التكاملات المعتلة وخواصها ودراسة اختبارات التقارب لها. وركزت دراستنا على أهمية الدوال الخاصة جاما وبيتا من حيث اجراء التكاملات المعتلة مع مقارنة الحلول باستخدام طرق التكامل المتعارف عليها، واعتمدت الدراسة على جمع البيانات من الكتب والمراجع الدولية والمجلات البحثية والتي أوصلتنا إلى نتائج تؤكد أن دالتي جاما وبيتا تسهم بطريقة رائعة جدا في تسهيل كثير من الحسابات العملية الصعبة المتعلقة بموضوع الدراسة. كما تقدم طريقة ناجحة لتوفير الوقت والجهد لحل المسائل الخاصة بالتكاملات المعتلة بل أن بعض هذه التكاملات لا يمكن حلها إلا باستخدام دالتي جاما وبيتا